Trauma and Health: Physical Health Consequences of Exposure to Extreme Stress. 2004
DOI: 10.1037/10723-008
|View full text |Cite
|
Sign up to set email alerts
|

Somatization and multiple idiopathic physical symptoms: Relationship to traumatic events and posttraumatic stress disorder.

Abstract: Physical symptom syndromes following war and other traumatic events have gone by an array of colorful labels over the past 150 years, and our medical and societal penchant for relabeling these syndromes continues to this day (see Table 8.1;Hyams, Wignall, & Roswell, 1996;Shorter, 1992; Schnurr & Green, chap. 1, this volume). Yet after many years of research, debate, and medical efforts, we are still far from a thorough etiologic or therapeutic understanding of these syndromes. The mainstream tradition in medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 85 publications
2
23
0
1
Order By: Relevance
“…Exposure to trauma is associated with illness behaviors, such as somatic symptoms (Engel, 2004; Green & Kimerling, 2004) and seeking medical care (Walker et al, 2004). There are multiple hypotheses that may explain why trauma may increase negative health perceptions and illness behavior (e.g., Ford 1997; Rodin et al, 1988; van der Kolk, 1994), including biological changes associated with trauma exposure, focusing on physical symptoms diverts attention from the trauma (i.e., focusing on physical symptoms is less distressing than focusing on psychological distress), and secondary gain (i.e., reporting physical symptoms may elicit help and support; Pennebaker, 2000; Schnurr & Green, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to trauma is associated with illness behaviors, such as somatic symptoms (Engel, 2004; Green & Kimerling, 2004) and seeking medical care (Walker et al, 2004). There are multiple hypotheses that may explain why trauma may increase negative health perceptions and illness behavior (e.g., Ford 1997; Rodin et al, 1988; van der Kolk, 1994), including biological changes associated with trauma exposure, focusing on physical symptoms diverts attention from the trauma (i.e., focusing on physical symptoms is less distressing than focusing on psychological distress), and secondary gain (i.e., reporting physical symptoms may elicit help and support; Pennebaker, 2000; Schnurr & Green, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Engel, 2004; Spitzer et al 2009), including in two recent studies of WTC responders (Niles et al 2011; Wisnivesky et al 2011). There are at least three explanations for this link.…”
Section: Introductionmentioning
confidence: 99%
“…White and Faustman (1989) examined the medical records of male veterans seeking inpatient treatment for PTSD and found that 42% of the sample had evidence of multiple medical problems, with 25% of the veterans suffering from musculoskeletal or pain problems. However, there is evidence that self-reports of pain are higher in individuals with PTSD compared to individuals without PTSD, even in the absence of objective assessments of physical injury (Asmundson & Norton, 1995;McFarlane et al, 1994;Shalev et al, 1990), perhaps indicating that somatization may be more common among people with PTSD (see also, Engel, 2004). Beckham and colleagues (1997) investigated rates of chronic pain and somatization in veterans seeking outpatient PTSD treatment using self-reports of PTSD symptom severity, depression, pain, pain-related disability, and measures of somatization.…”
mentioning
confidence: 96%